2020
DOI: 10.22271/fish.2020.v8.i5a.2299
|View full text |Cite
|
Sign up to set email alerts
|

Performance of largemouth bass Micropterus salmoides (Lacépède, 1802), fed fishmeal-and fish oil-free diets

Abstract: Diets were manufactured for largemouth bass (LMB) replacing fishmeal (FM) with poultry by-product meal (PBM), soybean meal (SBM), and a hydrolyzed soy meal. Experimental diets included a FM control (FMC), and three FM-free formulations containing equal amounts of PBM and SBM with fish oil (diet F2), Algal meal DHA (F3) or a soy protein concentrate (SPC). A commercial LMB diet was included for reference. Fish (n=20 per group) were randomly dispersed into one of 20 tanks with group weights of ±5%, and densities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…Higher dietary lipid is also often associated with elevated hepatosomatic indices (HSI), and although differences were observed among feed groups in the current trial, these did not reflect on diet composition. While fish from the diet supplemented only with canola oil (Diet 7) returned lowest values for HSI, which may indicate differences in energy partitioning, the general similarity in HSI, equivalence in intraperitoneal fat ratios and condition factors, and lack of effect of alternate oils on glycogen and lipid accumulation in other studies with LMB (McLean, Fredriksen, Alfrey, Craig, et al, 2020) imply equal utilization of the vegetable and algal oils.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Higher dietary lipid is also often associated with elevated hepatosomatic indices (HSI), and although differences were observed among feed groups in the current trial, these did not reflect on diet composition. While fish from the diet supplemented only with canola oil (Diet 7) returned lowest values for HSI, which may indicate differences in energy partitioning, the general similarity in HSI, equivalence in intraperitoneal fat ratios and condition factors, and lack of effect of alternate oils on glycogen and lipid accumulation in other studies with LMB (McLean, Fredriksen, Alfrey, Craig, et al, 2020) imply equal utilization of the vegetable and algal oils.…”
Section: Discussionmentioning
confidence: 74%
“…These results are remarkable because the Xinxin feed contained 15% higher and 20% lower levels of crude protein and lipid, respectively, than the experimental diets. The use of blended proteins, as illustrated here, combined with results from other successful studies with LMB, where major proportions of dietary FM were replaced (McLean, Fredriksen, Alfrey, Craig, et al, 2020; McLean, Fredriksen, Alfrey, Tlusty, et al, 2020; Ren et al, 2018; Subhadra et al, 2006b; Tidwell et al, 2005; Wang et al, 2018; Yi et al, 2020;), provides strong and realistic support to suggest that future LMB grower feeds can be formulated devoid of FM. LMB have been reported to respond positively to increasing levels of dietary lipid, with fish expressing increased weight gain, improved feed efficiency and protein‐sparing action (Anderson et al, 1981; Guo et al, 2019; Li et al, 2020a).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…SBM‐based diets have also been reported to damage the liver of Florida and snubnose pompanos expressing increased vacuolization and inflammation (Novriadi et al, 2018; Novriadi, Salze, et al, 2019; Pham et al, 2021). In the present study, the preceding negative consequences of soybean/corn inclusion were not evaluated and, although their occurrence cannot be excluded, the recorded lack of impact of the experimental diets on growth would suggest that Florida pompano are insensitive to the level of SPC/CPC (~14%) used herein, or that perhaps only a transitory effect arose, as previously considered for sea bream (Santigosa et al, 2010), carp (Urán et al, 2008) and largemouth bass (McLean et al, 2020). Alternatively, the use of a blend of proteins may have tempered the presence and potential for negative effects of ANFs, such as enzyme inhibitors.…”
Section: Discussionmentioning
confidence: 95%
“…Another study [ 44 ] evaluated feed enhancement components for juvenile LMB at 29.6 °C over eight days but did not record growth or FCR data. Concerning experimental data on commercial feed, one study [ 45 ] reported that LMB juveniles fed a commercial diet (Classic Bass ® , extruded, floating; protein/fat: 48/18; Skretting, Tooele, UT, USA) yielded an FCR of 1.06 in a recirculating system at approximately 28 °C for eight weeks. Another study by Tidwell et al [ 46 ] reported FCR values from 1.9 to 2.4 during the summer months, when temperatures were between 30 and 20 °C from May to August, for LMB juveniles cultured in 120.04 ha ponds on test diets.…”
Section: Discussionmentioning
confidence: 99%